Digital tools for gamification of the educational process of junior school students in conditions of distance learning - Pobryzghaieva, Valentyna; Nalyvaiko, Oleksii (Educological discourse, 2024)
The article examines the role of digital gamification tools in the educational process of junior high school students in the conditions of forced distance learning. The main online platforms and digital learning tools used during forced distance learning are highlighted, in particular: online learning platforms (Storyboard, Ed Puzzle, Edugames), mobile digital applications (MinecraftEdu, BookWidgets). The concept of gamification is defined as a powerful tool for engaging and motivating primary students, which refers to the process of adding game elements or mechanics to the learning process, which promotes the development of various cognitive skills, such as spatial imagination, imagination, reaction and mental abilities, which is of particular importance in children of primary school age. Gamification turns out to be an important strategy in distance learning, as it is aimed at engaging students in learning tasks. It was considered that one of the key advantages of using digital gamification tools is the possibility of increased individualization of training. This allows you to adapt the tasks to the level of development of each student, providing a personalized approach. Also, graphic and visual elements of gamification make learning more exciting and understandable for children, creating a positive attitude towards learning. Digital tools facilitate interaction and social support between students, even at a distance. They can include online team tasks that develop skills in collaboration and information sharing. In the absence of face-to-face contact, teachers can use digital gamification tools to effectively monitor student progress and provide quick feedback. This allows to identify and solve the learning difficulties of students. The main requirements to ensure the implementation of the idea of introducing gamification into the educational process of elementary school include giving students the opportunity to learn from their mistakes and try to cope with the task again in case of failure, providing students with a mobile environment for independent learning, providing constant and instant feedback with each other and with the teacher, create interactive tasks or quests instead of homework. In general, we note that digital gamification tools are a necessary advantage in the conditions of forced distance learning to create a stimulating and effective environment that contributes to the learning and development of junior schoolchildren.